THE SYSTEM OF ARCHETYPAL IMAGES IN TEMUR POLATOV’S NOVEL “THE TAROZIY TURTLE” (TAMADDUN NURI JURNALI, 2025)
This article analyzes the system of archetypal images in Temur Polatov’s novel “The Taroziy Turtle” within the context of Eastern philosophy and Uzbek cultural thought.